2017
DOI: 10.1093/femsle/fnx045
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione affects the transport activity of Rhizobium leguminosarum 3841 and is essential for efficient nodulation

Abstract: As glutathione (GSH) plays an essential role in growth and symbiotic capacity of rhizobia, a glutathione synthetase (gshB) mutant of Rhizobium leguminosarum biovar viciae 3841 (Rlv3841) was characterised. It fails to efficiently utilise various compounds as a sole carbon source, including glucose, succinate, glutamine and histidine, and shows 60%–69% reduction in uptake rates of glucose, succinate and the non-metabolisable substrate α-amino isobutyric acid. The defect in glucose uptake can be overcome by addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Plants were incubated in a controlled-environment chamber with an 18h photoperiod (day/night temperature, 22 and 20 • C). For dry weight determination, plants were grown in a 2-L beaker filled with sterile vermiculite, watered with nitrogen-free nutrient solution and harvested at 7 weeks (Cheng et al, 2017). The shoot was removed from the root and dried at 70 • C in a dry-heat incubator for 3 days before being weighed.…”
Section: Plant Growth and Microscope Study Of Nodulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants were incubated in a controlled-environment chamber with an 18h photoperiod (day/night temperature, 22 and 20 • C). For dry weight determination, plants were grown in a 2-L beaker filled with sterile vermiculite, watered with nitrogen-free nutrient solution and harvested at 7 weeks (Cheng et al, 2017). The shoot was removed from the root and dried at 70 • C in a dry-heat incubator for 3 days before being weighed.…”
Section: Plant Growth and Microscope Study Of Nodulesmentioning
confidence: 99%
“…Rhizosphere colonization assays were performed as previously described (Cheng et al, 2017). Pea seedlings were grown for 7 days, as described above, for acetylene reduction, and inoculated with RLgmcA and RL3841 in the cfu ratios 1000:0, 0:1000, 1000:1000, and 10000:1000.…”
Section: Rhizosphere Colonizationmentioning
confidence: 99%
“…This deficiency in nutrient transport also detected in R. leguminosarum 3841, which fails to efficiently use various carbon sources such as glucose, succinate, glutamine and histidine, may trigger an early nodule senescence. This transport deficiency in R. leguminosarum 3841 gshB mutant strain is also associated to a lower BNF (Cheng et al, 2017). The LysR-type transcriptional regulator LsrB, required for nodulation, also regulates gshA gene expression through modification of cysteine residues (Luo et al, 2005;Tang et al, 2018) and gshB gene expression (Lu et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…The symbiotic interaction established between legumes and bacteria allows the plant to satisfy its needs in nitrogen. The use of a bacterial strain deficient in GSH production alters significantly the biological nitrogen fixation and the growth of M. sativa, P. vulgaris, and P. sativum during NFS (Harrison et al, 2005;Muglia et al, 2008;Taté et al, 2012;Cheng et al, 2017). Moreover, the electronic microscopy analyses suggested that SmgshB mutant strain is partially impaired in the bacteroid differentiation (Harrison et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation